Externalities in rural development: Evidence for China - Martin Ravallion (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
The paper tests for external effects of local economic activity on consumption and income growth at the farm household level using panel data from four provinces of post-reform rural China. The tests allow for nonstationary fixed effects in the consumption growth process. Evidence is found of geographic externalities, stemming from spillover effects of the level and composition of local economic activity and private returns to local human and physical infrastructure endowments. The results suggest an explanation for rural underdevelopment arising from underinvestment in certain externality-generating activities, of which agricultural development emerges as the most important.
Keywords: D91; R11; Q12; 330; consumption growth; income growth; externalities; panel data; rural China; Ländlicher Raum; Privater Haushalt; Konsum; Agrareinkommen; China